If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x = -7x + 9 Reorder the terms: -10x = 9 + -7x Solving -10x = 9 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -10x + 7x = 9 + -7x + 7x Combine like terms: -10x + 7x = -3x -3x = 9 + -7x + 7x Combine like terms: -7x + 7x = 0 -3x = 9 + 0 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| f(x)=0.2x^2+x | | 9x-7=5x+37 | | 5v+u=-17 | | 6-42x=168 | | 9=4x+7y | | 66x=1254 | | 5w+9-9w=2(w-6)+w | | d=3/2m(-87) | | 7.4n+2.2n=36 | | 2(-6+2)-14= | | n/12=---104 | | a-5/6=-1/5 | | y/3=-104 | | x/4-x/6=20 | | 7/15x3/10 | | 6x-5y+2z=-49 | | 6(3m-2)=20m | | 12-(x+4)=-2(x-1)-2 | | -95=n-30 | | 2(5y+13)-5.7=203 | | X/14=85 | | (2x-3/4)-(2x-1/3)=1 | | 8w-26=-6(w+9) | | 4+p=56 | | -t+6=-t+9 | | 6(v+7)=-7v-36 | | 2.6+3x=97.4 | | 6t+7+3t=5t+27 | | -3b-7=20 | | 7y-5-2y=-20 | | 20=4v+16 | | 5x-16=4x-6 |